1979
DOI: 10.1071/ar9790751
|View full text |Cite
|
Sign up to set email alerts
|

The use of non-carcass parts in the prediction of beef carcass composition on the slaughter floor

Abstract: Ninety-five steers were used to develop a method of estimating the weights or percentages of the four carcass tissues—muscle, bone, fat and connective tissue—while the carcasses were still on the slaughter floor. From an investigation of a number of non-carcass parts it was found that three measurements could be used to estimate all four carcass components. The measurements were (a) short-cut tongue weight; (b) foreshanks weight; (c) hot side weight. Simple and multiple regression equations were developed to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

1983
1983
2010
2010

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 13 publications
1
7
1
Order By: Relevance
“…During the course of the study, the following measurements were recorded: fasted live weight (after restricting the animals to water only for 24 h), hot carcass weight, and chilled carcass weight; fat thickness at the 12th rib and rump Pg fat thickness (Moon 1980), both recorded in Table 1; foreshanks weight (Johnson 1979) which is the weight of both foreshanks, disarticulated at the carpo-metacarpal joint and cleansed of impacted dirt and faeces from sole and inter-digital areas. Twelfth rib fat thickness is the subcutaneous fat thickness measured three-quarters of the distance from the medial to the lateral border of M. longissimus thoracis et lumborum.…”
Section: Dissection Techniquementioning
confidence: 99%
“…During the course of the study, the following measurements were recorded: fasted live weight (after restricting the animals to water only for 24 h), hot carcass weight, and chilled carcass weight; fat thickness at the 12th rib and rump Pg fat thickness (Moon 1980), both recorded in Table 1; foreshanks weight (Johnson 1979) which is the weight of both foreshanks, disarticulated at the carpo-metacarpal joint and cleansed of impacted dirt and faeces from sole and inter-digital areas. Twelfth rib fat thickness is the subcutaneous fat thickness measured three-quarters of the distance from the medial to the lateral border of M. longissimus thoracis et lumborum.…”
Section: Dissection Techniquementioning
confidence: 99%
“…Of the two, the intermandibular method, with a lower standard deviation of the mean difference between predicted and actual side fat weight, was slightly the superior predictor. Johnson (1979) demonstrated that the trimmed tongue could be used in multiple regression to predict side muscle weight on the slaughter floor, with an accuracy surpassed only by predictions using the weight of M. biceps femoris or M. longissimus, or combinations of the weights of either of these muscles or shin muscle group, with chilled side weight. In an effort to improve the accuracy of this technique by using entire trimmed muscles from the head, the current study failed to demonstrate any superior predictors, and served only to confirm the relative accuracy and convenience of the variables chosen by Johnson (1979) (trimmed tongue weight, hot side weight and fat thickness at the 12th rib) to predict side muscle weight.…”
Section: Prediction Of Bonementioning
confidence: 98%
“…Johnson (1979) demonstrated that the trimmed tongue could be used in multiple regression to predict side muscle weight on the slaughter floor, with an accuracy surpassed only by predictions using the weight of M. biceps femoris or M. longissimus, or combinations of the weights of either of these muscles or shin muscle group, with chilled side weight. In an effort to improve the accuracy of this technique by using entire trimmed muscles from the head, the current study failed to demonstrate any superior predictors, and served only to confirm the relative accuracy and convenience of the variables chosen by Johnson (1979) (trimmed tongue weight, hot side weight and fat thickness at the 12th rib) to predict side muscle weight. This simple technique, though never used in an Australian abattoir, lends itself to commercial application, since hot side weight and a fat thickness measurement are routinely recorded on the slaughter floor, whilst the tongue may be trimmed in a few seconds, also on the slaughter floor.…”
Section: Prediction Of Bonementioning
confidence: 98%
See 2 more Smart Citations